Sprouts for the Future: an Initial Review of Cicero and the Environment - Magnavacca, Adalberto (Ciceroniana On Line, 2023)
The corpus of Cicero's works, in its variety and vastness, lends itself to further research, but we are confident that the series of contributions presented at the Bologna conference and collected in this volume of the journal can trace some lines and fit fully into the contemporary debate.